2010
DOI: 10.1111/j.1439-0426.2010.01423.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic plasticity and mechano-transduction in the teleost skeleton

Abstract: The proper formation, growth and maintenance of many bones depends on the mechanical loads generated by gravity and muscles. Mechanical loading by muscle forces does not only affect bone growth and maintenance in adult and juvenile vertebrates, but also affects larval and embryonic bone development. We have reviewed the current understanding of mechanotransduction in birds and mammals and compared it to teleosts. The major mechanosensing cells in the adult mammalian and avian skeleton are osteocytes. They are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
42
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 57 publications
1
42
0
Order By: Relevance
“…Indeed, we found out that the effect of an increase of water velocity mainly induces changes in the developmental progress in all fins; the responsive elements ossify at comparatively smaller size at faster velocity. It is suggested that rearing fish in differential water velocity may affect their locomotion and thus may change the mechanical stress exerted on developing endoskeletal elements (Fischer-Rousseau et al, 2009;Cloutier et al, 2010;Fiaz et al, 2010Fiaz et al, , 2012. In this context, several lines of evidences have shown the correlative link between environmental changes such as differential water velocity and plasticity in timing of skeletogenesis (rather than changes in the relative order of developmental events) in fishes.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Indeed, we found out that the effect of an increase of water velocity mainly induces changes in the developmental progress in all fins; the responsive elements ossify at comparatively smaller size at faster velocity. It is suggested that rearing fish in differential water velocity may affect their locomotion and thus may change the mechanical stress exerted on developing endoskeletal elements (Fischer-Rousseau et al, 2009;Cloutier et al, 2010;Fiaz et al, 2010Fiaz et al, , 2012. In this context, several lines of evidences have shown the correlative link between environmental changes such as differential water velocity and plasticity in timing of skeletogenesis (rather than changes in the relative order of developmental events) in fishes.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of developing skeletal tissues, time is necessary to cope with environmental changes. However, fish endoskeleton is remarkable in that it develops relatively late in ontogeny compared to mammals and birds; most of it occurs after hatching (Fiaz et al, 2010;Saele and Pittman, 2010). Even post-hatching exposure to increased water velocity is sufficient to induce plastic responses in timing, primarily with respect to later formed bones and cartilages to a lesser extent.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations